EARTHQUAKE CATALOGS: EVALUATION OF DATA COMPLETENESS - Smirnov V.B. (My University, 1998)
The lowest magnitude of complete reporting and its variations in space and time are estimated for several regional earthquake catalogs. The discussion focuses on questions of methodology and the space-time inhomogeneity of real earthquake catalogs.